Social Conflicts Affecting Teaching and Learning in Public Primary Schools of Elgeyo Marakwet County, Kenya - Lulley , Salome (African Journal of Education,Science and Technology (AJEST), 2018)
Social-cultural factors have contributed to educational disparities in some areas in Kenya. A study was carried to determine the extent to which conflict affect teaching and learning in public primary schools in Elgeyo Marakwet County. The Bronfenbreńńers (1990) ecological systems theory was adopted. The Design was descriptive survey and the methodology used was mixed research method. Stratified sampling was used to stratify sub-counties in to those in Elgeyo and Marakwet then simple random sampling technique was used to select two sub- one from each stratum. Simple random sampling was used to select 80 public schools in Elgeyo Marakwet County. Simple Random sampling was used to select 48 class teachers, 24 parent representatives and 60 pupils from the sampled schools. Purposive sampling was used to sample the (2) Sub-Counties Education Officers and the Head teachers. A total of 80 Head teachers participated in the study. Data was collected by use of questionnaires and interviews. Data analysis was done through descriptive statistics which included application of percentages and frequency tables and graphs. Findings from this study established that social conflicts negatively affect teaching and learning in the County. It is recommended that those harmful cultural practices that influence teaching and learning should be abandoned and the community sensitized on alternative means and ways of mitigating the motivating factors. Also, concerted efforts by the government and other stakeholders should be made so that conflicts are minimised. The findings from this study will be utilized by the Ministry of Education and line agencies to adequately plan and formulate policies oriented towards enhanced strategies for promoting students’ teaching and learning.